Analysis Of Teacher Readiness And Provision Of Infrastructure In Implementing The Independent Curriculum At SMA Negeri 1 Lembang Jaya (Bakoba : Journal of Social Science Education, 2023)
The background of this research is the readiness of schools and teachers in implementing the independent curriculum, so that learning objectives can be achieved effectively and efficiently. The purpose of this research is to see what schools, teachers and in terms of the facilities and infrastructure available at SMA Negeri Lembang Jaya have to prepare to support the learning process. In addition, this study also aims to assess how far the implementation of the independent curriculum has been implemented by SMA Negeri 1 Lembang Jaya. The method used in this research is descriptive qualitative method. The results of this study indicate that readiness in implementing the independent learning curriculum is not only seen from the readiness of teachers and students, but also by looking at the readiness of schools and facilities and infrastructure that will support the implementation of fun learning. So it can be concluded that SMA Negeri 1 Lembang Jaya is a school that implements a level 2 independent curriculum, namely independent change. Schools and teachers make changes independently without financial assistance from the government. Teachers conduct training on the independent teaching platform independently so that teachers better understand how the independent curriculum is implemented in schools and what the teacher's assessment process is.